التجارة الالكترونية في الفقه الاسلامي نموذج دروب شيبينيغ - بالطاهر, الزهرة; بن تواتي, خديجة (University of Eloued-جامعة الوادي, 2022)
"موضوع الرسالة المعروف ب:"" التجارة الالكترونية في الفقه الاسلامي نموذج دروب شيبينغ "" ، و الإشكالية الرئيسية التي أزلنا اللبس عنها والتي تدور حول معرفة أحكام التجارة الالكترونية . وقد جاء الموضوع في ثلاثة فصول : خصص أولها ببيان ماهية التجارة الالكترونية ، وجعل ثانيها لصور التجارة الالكترونية وأحكامها في الفقه الاسلامي ، بينما سلط ثالثها لنموذج دروب شيبينغ وبيان أهم أحكامه الشرعية . ومن النتائج الأساسية التي توصلنا إليها أن التجارة الالكترونية من المعاملات المستجدة في زماننا هذا وهي تعد في مرتبة الضروريات ، مما أوصى البحث بوجوب الاهتمام بالأبحاث المتعلقة بالواقعات المستجدة من الناحية الفقهية ."Abstract the thesis theme that known as the E-commerce in Islamic jurisprudence(drop shipping as a model)which we made it clear and which is about knowing the Islamic provisions of E-commerce we discussed this subject in three different chapters the first chapter(1) include the definition of E-commerce and in the second chapter(2) we talked about the different kinds of the Islamic provisions of E- commerce and in the third chapter an example model of the drop shipping and it most Islamic provisions we came up with a significant results which let are develop treatments which are one of the necessities I highly recommend in having more interest with the researches that are related to the realistic issues from an Islamic perspective
مذكرة ماستر
Keywords: التجارة الالكترونية - الفقه الاسلامي - نموذج دروب شيبينيغ; Electronic commerce - Islamic jurisprudence - Dropshipping model